Botulinum toxin injection changes resting state cerebellar connectivity in cervical dystonia - Hok, Pavel; Hvizdošová, Lenka; Otruba, Pavel; Kaiserová, Michaela; Trnečková, Markéta; Tüdös, Zbyněk; Hluštík, Petr; Kaňovský, Petr; Nevrlý, Martin (Scientific reports, 2021)
In cervical dystonia, functional MRI (fMRI) evidence indicates changes in several resting state networks, which revert in part following the botulinum neurotoxin A (BoNT) therapy. Recently, the involvement of the cerebellum in dystonia has gained attention. The aim of our study was to compare connectivity between cerebellar subdivisions and the rest of the brain before and after BoNT treatment. Seventeen patients with cervical dystonia indicated for treatment with BoNT were enrolled (14 female, aged 50.2 ± 8.5 years, range 38-63 years). Clinical and fMRI examinations were carried out before and 4 weeks after BoNT injection. Clinical severity was evaluated using TWSTRS. Functional MRI data were acquired on a 1.5 T scanner during 8 min rest. Seed-based functional connectivity analysis was performed using data extracted from atlas-defined cerebellar areas in both datasets. Clinical scores demonstrated satisfactory BoNT effect. After treatment, connectivity decreased between the vermis lobule VIIIa and the left dorsal mesial frontal cortex. Positive correlations between the connectivity differences and the clinical improvement were detected for the right lobule VI, right crus II, vermis VIIIb and the right lobule IX. Our data provide evidence for modulation of cerebello-cortical connectivity resulting from successful treatment by botulinum neurotoxin.
Keywords: kognice; lidé; botulotoxiny typu A; magnetická rezonanční tomografie; výsledek terapie; Adult; Middle Aged; Cognition; Torticollis; tortikolis; Magnetic Resonance Imaging; stupeň závažnosti nemoci; Female; mozková kůra; mozeček; Botulinum Toxins, Type A; Cerebellum; Rest; Humans; Injections, Intralesional; odpočinek; lidé středního věku; mužské pohlaví; Cerebral Cortex; ženské pohlaví; Severity of Illness Index; Treatment Outcome; Male; injekce do léze; dospělí